Getting a handle on glycogen synthase – Its interaction with glycogenin. (December 2015) - Zeqiraj, Elton; Sicheri, Frank
Abstract: Glycogen is a polymer of glucose that serves as a major energy reserve in eukaryotes. It is synthesized through the cooperative action of glycogen synthase (GS), glycogenin (GN) and glycogen branching enzyme. GN initiates the first enzymatic step in the glycogen synthesis process by self glucosylation of a short 8–12 glucose residue primer. After interacting with GN, GS then extends this sugar primer to form glycogen particles of different sizes. We discuss recent developments in the structural biology characterization of GS and GN enzymes, which have contributed to a better understanding of how the two proteins interact and how they collaborate to synthesize glycogen particles.